Windows into Canine Leishmaniasis: From Veterinary Diagnosis to Promising In Vitro Models to Target Parasite-Secreted Lipid Bound Vesicles - Áurea Martins Gabriel; Gilvando Rodrigues Galvão; Adan Galué-Parra; Lívia Medeiros Neves Casseb; Washington Luiz Assunção Pereira; Ketil Winther Pedersen; Délia Cristina Figueira Aguiar; Evonnildo Costa Gonçalves; Edilene O. Silva (2024)
Leishmaniases are zoonotic vector-borne diseases caused by a wide variety of Leishmania species with complex transmission cycles involving different reservoirs, potential new hosts and vectors. Similarly, to other eukaryotes, Leishmania release extracellular vesicles (LEVs) to play important initial interactions that are crucial to modulate the subsequent systemic immune response on the establishment of infection in humans and others hosts like dogs. Recent studies in endemic areas of Brazil concluded that canine infections were predominantly due to L. amazonensis and not restricted to L. infantum (syn. Leishmania chagasi). Under these premises, the diagnosis of leishmaniasis needs to be improved with the identification of current etiological agent and the histopathologic features, highlighting the differential diagnosis and the molecular components of LEVs. In this way, the dual aim of that study is to register collected observations of natural canine infections, enhancing the relevance of differential diagnosis in companion animals and inserting in vitro results in the field of LEVs that still research gaps to be filled to understand the mechanisms and biological aspects involving the parasite-host interactions. Therefore, improve these studies of Parasitology research is important for diagnostic, prognostic, treatment advances and continuing need for global prevention, control, elimination/eradication of these parasitic infections.